PRAXEOLOGICAL ASPECTS OF THE APPLICATION OF LEGAL SCIENCE AND INNOVATIVE TECHNOLOGIES FOR FLIGHTS OF THE FUTURE - Lykhova, Sofiia; Bilenchuk, Petro; Obikhod, Tetiana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to establish the praxeological aspects of the application of jurisprudence and innovative technologies for the aircraft of the future and to develop specific recommendations for improvement on this basis. Research methods: a comprehensive analysis of static data, scientific literature and the practice of applying legislation was used. Results: modern statistics on the safety of aviation use in everyday life are provided. Prospects for the development of aircraft construction are presented. The latest achievements of unmanned aerial vehicles in the economic and scientific fields as promising directions for the development of aerial vehicles are studied. Vulnerable aspects of drones and methods of overcoming relevant dangers, including cyber threats, are presented. It is substantiated that modern technologies play a key role in the development of aviation, contributing to increasing the efficiency, safety and environmental friendliness of aircraft. It has been established that modern technologies of strategic planning and conceptual design ensure the effectiveness of integrated management structures of aviation science and technological developments, which is a key factor for maintaining a leading role in the field of aviation and aerospace. Discussion: the future improvement of the aviation industry is linked to the issues of flight safety and prevention of aviation accidents, which relate to technical, human and organizational factors; medical support and health of the flight crew for the prevention of occupational diseases and maintenance of the working capacity of pilots; development of new materials and technologies to reduce weight and increase the efficiency of aviation equipment; environmental problems related to aviation noise and emissions; economic and social issues of the development of the aviation industry, including pricing, competition and passenger service.